Biology of edible bivalve and gastropod from Sarawak Malaysia: morphology, distribution and population genetic - Idris, Mohd Hanafi; Hamli, Hadi (LAP Lambert Academic Publishing, 2014)
This book is the outcome of three years of master research on edible bivalve and gastropod at Sarawak, Malaysia. There are many species of mollusc that being consumed by the local people in Sarawak as the daily protein source. Mollusc also contributes to the local economic value particularly for people that depending only from natural resource. This book provides information regarding mollusc species, morphology characters and genetic diversity. It is aimed as technical reference and baseline study for students, researchers, professionals and managers of the fisheries resource management.